Explore Titanic - Chrisp, Peter; Vongprachanh, Somchith (Hauppauge, NY : Barron's, 2011)
Contains approximately 125 photographs and illustrations, including numerous three-dimensional images, that explore the Titanic from its first launch in 1911 to its tragic fate.
7.5
3-6
System requirements not stated.
Keywords: Titanic (Steamship) -- Juvenile literature; Shipwrecks -- North Atantic Ocean -- Juvenile literature; Titanic (Steamship); Shipwrecks; Titanic (Steamship); Shipwrecks